(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Some ionic and biochemical responses of lentil (Lens culinaris Medik.) under phosphorus deficient condition were studied. Seedlings were raised in solution culture containing phosphorus and without phosphorus (P-deficiency). Phosphorus deficiency decreased Ca2+ and Fe2+ accumulation and slightly decreased Mg2+ accumulation in root and shoot of lentil. Phosphorus deficiency caused a decrease in accumulation of total sugars in leaf and stem but increased in root. Accumulation of total soluble proteins was depressed in lentil following P-deficiency treatment. Phosphorus deficiency increased total amino acid contents in both root and shoot. DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15315 J. Asiat. Soc. Bangladesh, Sci. 38(1): 1-6, June 2012